Russian mass media in Kazakhstan information society: sociological research (Herald of Journalism, 2018)
The article reflects the role of the Russian mass media in the information space of Kazakhstan, andgives statistics on the number of Russian media in the Republic over the past five years. The authorconducted sociological studies, interviewing political scientists on the impact of Russian media on thecitizens’ public consciousness. The results of the study revealed the prevalence of Russian media in theterritory of Kazakhstan and the level of their influence on public consciousness. The author also identifiedthe trends in the Kazakh media evolution, the prospects for their activities in preserving the nationalidentity of the people of Kazakhstan.